WHEN DIGITAL FOOTPRINTS ARE NO LONGER VALID: AN ANALYSIS OF DIGITAL FORENSIC EVIDENCE FAILURE IN LEGAL PROCEEDINGS: Study Case: Online Gambling 2020 - Ashuri; Hendratna Mutaqin (Journal of Golden Generation Legal Science, 2026)
The advancement of digital technology has brought significant changes to the legal system, particularly in the use of electronic evidence as a means of proof in court. However, the validity of digital forensic evidence is often questioned due to various technical, procedural, and legal challenges. This study aims to analyze the factors contributing to the failure of digital forensic evidence in legal proceedings and to formulate recommendations for improving its validity. The method used is a Systematic Literature Review (SLR) by examining various academic sources that discuss issues of digital evidence validity, forensic standards, and emerging legal challenges. The results of the study indicate that the failure of digital evidence generally stems from non-compliance in the processes of data collection and preservation with chain of custody standards, insufficient competence of law enforcement officers in digital technical aspects, and conflicts between legal requirements and data privacy regulations, such as the GDPR and CCPA. The case study of online gambling 2020, at the South Jakarta District Court confirms that the absence of forensic verification and chain of custody documentation caused the digital evidence to lose its probative value. Therefore, it is necessary to establish standardized forensic procedures, provide training and certification for law enforcement officials and forensic experts, and develop national guidelines for managing digital evidence aligned with international standards. This research is expected to contribute to strengthening the integrity and validity of digital evidence, thereby enhancing the enforcement of justice in the digital era.